Approach for teaching grammar in iban secondary school textbooks - Felisia, Tensing (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study examined the approach to teaching grammar in Iban secondary school textbooks. The specific objectives were to identify the grammar items focused, the types of grammar practices and the grammar approach employed based on the grammar features and flow of activities in the grammar sections. The 5 selected textbooks were the official and compulsory teaching and learning materials used in Iban educational setting, which were provided by Ministry of Education Malaysia and designed according to the national curriculum. Decoo‟s (1996) refinement of inductive and deductive approach to five modalities were adapted as the checklists for the analysis. The findings showed that the grammar items focused on the learning of language parts and structures, the grammar practices found were the mechanical types which involved heavy drills and controlled production, while Decoo‟s Modality A (Actual Deduction) or known as deductive approach were the dominant teaching used in all the 5 textbooks. It was found that Form 5 textbook was entirely deductive compared to Form 2 with the ratio of 1:24, Form 3; 1:3.85, Form4; 1:7 and Form 1; 1:2.25. Therefore, the result indicated that Iban grammar teaching reflected the structural view of language learning. The findings of the study would provide beneficial feedback to the organisations and educationists involved in the material development and manipulation, which specifically refers to Iban language.